2014
DOI: 10.1038/eye.2014.153
|View full text |Cite
|
Sign up to set email alerts
|

A safety audit of the first 10 000 intravitreal ranibizumab injections performed by nurse practitioners

Abstract: Purpose To evaluate the safety of a nurse practitioner (NP)-delivered injection service for the treatment of wet age-related macular degeneration (wAMD) with ranibizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 11 publications
2
27
0
1
Order By: Relevance
“…Under a system where nurses only injected favourable cases, they achieved safety rates comparable to those of physicians in training. Simcock et al (2014) reported recently similar findings in their study.…”
Section: Discussionsupporting
confidence: 79%
“…Under a system where nurses only injected favourable cases, they achieved safety rates comparable to those of physicians in training. Simcock et al (2014) reported recently similar findings in their study.…”
Section: Discussionsupporting
confidence: 79%
“…Since complications would have to be very severe if they were to be reflected on a mean best-corrected visual acuity change, we studied the relative distribution of ocular adverse events such as lens damage, retinal detachment and endophthalmitis. The incidence of endophthalmitis (0.5& per injection) was similar to the incidence in the Comparison of Age-related Macular Degeneration Treatments Trial (Martin et al 2011) where all injections were physician-administered and also to observational studies from Denmark and the UK with 12 000 nurse-administered intraocular injections each (Simcock et al 2014;Hasler et al 2015). No lens damage or retinal detachments were observed during the study.…”
Section: Discussionsupporting
confidence: 70%
“…The rising number of intraocular injections, expected to continue according to projections of the increase in the elderly population, (United Nations 2017) has become a challenge for ophthalmology departments worldwide. Task shifting to nurse-administered injections may alleviate this burden (Browning 2018), and observational studies indicate this might be safe and acceptable to patients (Varma et al 2013;DaCosta et al 2014;Michelotti et al 2014;Simcock et al 2014;Hasler et al 2015). However, no randomized controlled trial (RCT) has earlier investigated whether such a task shift can be performed without increased risk to visual function.…”
Section: Introductionmentioning
confidence: 99%
“…Nurse injectors have been demonstrated to be able to provide a safe and effective injection service that is well received by patients. 9,19 Costs to the NHS and drug label status were of the least importance to patients and this has potential important consequences to the way off-label drugs are used. There is much in the recent literature debating the use of off-label anti-VEGF agents due to their significant cost saving.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition to the issue of cost, there is the issue of workload with an increasing number of units turning to the use of nursing staff to perform the intraocular injections 9 and issues as to whether it is appropriate to inject patients on the same day as their assessment clinic.…”
Section: Introductionmentioning
confidence: 99%